Correlation among Personality and Self-Concept to Storytelling Ability - Istnain Alfajri Husain; Aris Suziman (Jurnal Sultra Elementary School, 2020)
Abstract: This research  aimed to determine the Correlation of (1) the personality to storytelling ability, (2) self-concept to storytelling ability, (3) personality and self-concept together to storytelling ability. This research was conducted in TK B Islam Kemaraya, TK B Mekar Indah Kendari and TK B Aisyiyah Kendari. The data analysis techniqueus is the multiple correlation analysis. The results showed that there is a correlation of (1) the personality to storytelling ability, (2) self-concept to storytelling ability, (3) personality and self-concept together to storytelling ability.This implies the storytelling ability can be improved by enhancing personality and  self-concept.Keyword: personality, self-concept, Storytelling  ability